WORKSHOP ON DEVELOPING INTERACTIVE LEARNING MEDIA FOR GURU PENGGERAK USING ARTICULATE STORYLINE 3 IN BANDUNG - Dahlan, Taufiqulloh; Dheni Harmaen; Acep Roni Hamdani; Erni Kustiani (LPM Universitas Pasundan, 2024)
This community engagement program (PKM) is designed to support